RISIKO POLA MAKAN TERHADAP KEJADIAN APENDISITIS DI RSUD DR. H. CHASAN BOESIRIE TERNATE - Ferdian Hidayat; Abd Hakim Husen (NHM PRESS, 2022)
This study aims to analyze the relationship between diet and the incidence of appendicitis in RSUD DR. H. Chasan Boesirie Ternate. This type of research was an analytic observational using a case-control design involving 70 patients with appendicitis at Dr H. Chasan Boesirie Hospital Ternate who were selected by purposive sampling which were divided into 2 groups, namely 35 patients as cases and 35 patients as controls. The research variables in this study consist of the dependent variable and the second is the independent variable. Data analysis uses the Odds Ratio test because the research data is categorical. Variables that have a p-value <0.05 are considered significant. The conclusion of the study was that there were significant differences between the eating patterns in the case group and the control group. Someone who has a poor diet has the opportunity to suffer from appendicitis 14 times.